2003
DOI: 10.1074/jbc.m309127200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fatty Acid Composition of Dopaminergic Neurons Expressing α-Synuclein and Human Brains with α-Synucleinopathies

Abstract: ␣-Synuclein (␣S) is an abundant neuronal protein that accumulates in insoluble inclusions in Parkinson's disease (PD) and the related disorder, dementia with Lewy bodies (DLB).A central question about the role of ␣S in the pathogenesis of PD and DLB concerns how this normally soluble protein assembles into insoluble aggregates associated with neuronal dysfunction. We recently detected highly soluble oligomers of ␣S in normal brain supernatants and observed their augmentation in PD and DLB brains. Further, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
189
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(209 citation statements)
references
References 40 publications
16
189
3
1
Order By: Relevance
“…These results are consistent with those observed for uptake of 16:0 into brains lacking α-synuclein (29) and with its affect on 20:4n-6 and 16:0 uptake and metabolism in primary astrocytes (11). Brain cytosolic, unesterified polyunsaturated fatty acid mass is reduced when α-synuclein is absent (88), suggesting a connection between α-synuclein expression and polyunsaturated fatty acids. The observed reduction in targeting to the organic fraction is accounted by reduced incorporation coefficients for 20:4n-6 into individual brain phospholipids in Snca -/-mice.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with those observed for uptake of 16:0 into brains lacking α-synuclein (29) and with its affect on 20:4n-6 and 16:0 uptake and metabolism in primary astrocytes (11). Brain cytosolic, unesterified polyunsaturated fatty acid mass is reduced when α-synuclein is absent (88), suggesting a connection between α-synuclein expression and polyunsaturated fatty acids. The observed reduction in targeting to the organic fraction is accounted by reduced incorporation coefficients for 20:4n-6 into individual brain phospholipids in Snca -/-mice.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are well in agreement with previous data published for frontal cortex in PD pathology (20,54) and indicate increased levels of peroxidable fatty acids. These results demonstrate that, while in whole cortical tissues from PD brains, there are increased levels of LCPUFAs (particularly DHA), their presence in lipid rafts was dramatically reduced.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, elevated PUFA levels have been detected in the soluble fractions of PD and Lewy bodies dementia brains. The levels of saturated and monounsaturated fatty acids did not change in these PD brains or in cells overexpressing -synuclein, which indicated thatsynuclein is involved specifically in the maintenance of PUFA levels (Sharon et al, 2003b). Using binding assays, it has been demonstrated that -synuclein binds saturably and with high affinity to detergent-resistant membranes, to lipid rafts, in permeabilized HeLa cells, and in the presence of synaptosomal membranes from transgenic mice expressing humansynuclein.…”
Section: Membrane Interactions In Vivomentioning
confidence: 99%